Legal Liability of Parents in Family Law Matters - Vasilyi Aleksandrovich Tsvetkov (Сибирское юридическое обозрение)
The article deals with the relationship of protection and measures of parental responsibility. Forms of parental responsibility are also considered. The author analyses ways to protect children from parental misconduct and summarizes practices in courts regarding family and legal responsibilities of parents in Omsk region.